2017
DOI: 10.5489/cuaj.4271
|View full text |Cite
|
Sign up to set email alerts
|

A prospective audit on the effect of training and educational workshops on the incidence of urethral catheterization injuries

Abstract: Introduction: The incidence of iatrogenic urethral catheterization (UC) injuries is approximately 0.3%. Resultant complications are associated with patient morbidity and unnecessary healthcare costs. Our aim was to investigate whether educational training workshops decreased the incidence of UC-related injuries. Methods: A prospective audit was performed to calculate incidence, morbidity, and costs associated with iatrogenic UC injury from January to July 2015. Educational workshops were then conducted with he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 9 publications
1
23
0
1
Order By: Relevance
“…A lack of regular inspection of procedural-based skills such as catheterisations by senior staff may a contributory factor. 5 In addition, a decline in undergraduate exposure to urology may contribute to the difficulties that foundation year doctors face. However, it is not limited to the UK and is not a new problem, as Benson et al previously demonstrated that 15% of new graduates had never experienced a rotation in urology.…”
Section: Dear Mr Pearcementioning
confidence: 99%
See 4 more Smart Citations
“…A lack of regular inspection of procedural-based skills such as catheterisations by senior staff may a contributory factor. 5 In addition, a decline in undergraduate exposure to urology may contribute to the difficulties that foundation year doctors face. However, it is not limited to the UK and is not a new problem, as Benson et al previously demonstrated that 15% of new graduates had never experienced a rotation in urology.…”
Section: Dear Mr Pearcementioning
confidence: 99%
“…7 Bhatt et al have conducted a large audit on iatrogenic catheter injuries and noted an incidence of 4.3/1000. 5 They also introduced a practical compulsory male catheterisation session for all newly qualified house officers, supervised by a member of the urology team. 5 Following this novel idea a reduction in catheter-related injuries was noted.…”
Section: Dear Mr Pearcementioning
confidence: 99%
See 3 more Smart Citations